Blood flow redistribution and ventilation-perfusion mismatch during embolic pulmonary arterial occlusion. - Burrowes, K; Clark, A; Tawhai, M (2011)
Acute pulmonary embolism causes redistribution of blood in the lung, which impairs ventilation/perfusion matching and gas exchange and can elevate pulmonary arterial pressure (PAP) by increasing pulmonary vascular resistance (PVR). An anatomically-based multi-scale model of the human pulmonary circulation was used to simulate pre- and post-occlusion flow, to study blood flow redistribution in the presence of an embolus, and to evaluate whether reduction in perfused vascular bed is sufficient to increase PAP to hypertensive levels, or whether other vasoconstrictive mechanisms are necessary. A model of oxygen transfer from air to blood was included to assess the impact of vascular occlusion on oxygen exchange. Emboli of 5, 7, and 10 mm radius were introduced to occlude increasing proportions of the vasculature. Blood flow redistribution was calculated after arterial occlusion, giving predictions of PAP, PVR, flow redistribution, and micro-circulatory flow dynamics. Because of the large flow reserve capacity (via both capillary recruitment and distension), approximately 55% of the vasculature was occluded before PAP reached clinically significant levels indicative of hypertension. In contrast, model predictions showed that even relatively low levels of occlusion could cause localized oxygen deficit. Flow preferentially redistributed to gravitationally non-dependent regions regardless of occlusion location, due to the greater potential for capillary recruitment in this region. Red blood cell transit times decreased below the minimum time for oxygen saturation (<0.25 s) and capillary pressures became high enough to initiate cell damage (which may result in edema) only after ~80% of the lung was occluded.